Association Between Dietary Inflammatory Index and NAFLD: A Cross-Sectional Study of the National Health and Nutrition Examination Survey - Yuan He; Yuhang Yang; Pengfei Cheng; Wei Zhang; Jinghan Jia; Dawei Ye; Jinxi Wang (Mediators of Inflammation)
Conclusions: A proinflammatory diet is associated with the development of NAFLD, and we recommend improving diet to reduce the risk of developing liver disease, especially NAFLD.